THE RELATIONSHIP BETWEEN COGNITIVE AND AFFECTIVE EMPATHY AND EMOTIONAL INTELLIGENCE IN HIGH SCHOOL STUDENTS(IN THE CONTEXT OF THE REPUBLIC OF UZBEKISTAN) (Universal International Scientific Journal, 2026)
This article presents a study of the relationship between cognitive and affective empathy and emotional intelligence (EI) in high school students at School No. 1 in Tashkent, Uzbekistan. Based on a sample of 30 students (16 boys and 14 girls, aged 15–17), using D. Goleman's questionnaire and V. V. Boyko's methodology, it was found that the majority of respondents demonstrated moderate levels of empathy and EI. Correlation analysis (Spearman's rho) revealed significant positive relationships: cognitive empathy correlates with self-awareness (ρ = 0.54; p < 0.01) and social awareness (ρ = 0.61; p < 0.01), while affective empathy correlates with self-regulation (ρ = 0.46; p < 0.01) and social skills (ρ = 0.52; p < 0.01). The novelty of the study lies in the context of Uzbekistan, where UNESCO social and emotional learning (SEL) programs emphasize the role of EI in education, and in the analysis of gender differences: girls show higher rates of affective empathy, which is consistent with the work of A. N. Pevneva on the role of empathy in professional development. The results can be used to develop emotional competence programs, promoting the advancement of women in psychology and education.
Keywords: cognitive empathy, affective empathy, emotional intelligence, high school students, Uzbekistan, gender differences.